Neutrophil Lymphocytes Ratio (NLR) of One-Step and Multi-Step Procedure for Hirschsprung Disease Patients At Arifin Achmad General Hospital - Dita Kartika Sari; TB Odih Rhomdani Wahid; Ismar Ismar; Laode Burhanuddin; Yolla Fitri Elmi (Fakultas Kedokteran Universitas Riau, 2024)
Hirschsprung disease (HD) is a congenital anomaly due to intestinal aganglionosis starting from the internal anal sphincter and spreading to the proximal area with varies extension of the segment. Definitive treatment for this abnormality is to perform surgery to remove the aganglionic bowel and can be carried out in one-step and multi-step procedure. In the process of wound healing after surgery, it involves inflammatory mediators as a marker of whether there is a stress response from the endocrine system such as neutrophil-lymphocyte ratio (NLR). This study aims to compare NLR as an inflammatory biomarker in one-step and multi-step procedure of hirschsprung disease patients at Arifin Achmad Hospital. The design of this study was cross-sectional using medical records and using total sampling for number of samples. Age, gender, and method of surgery were evaluated by univariate and bivariate to determine whether there were statistical differences. Seven HD patient taken from Mei-October at Arifin Achmad Hospital taken for evaluated. The results showed that the most samples were in < 1-month-old (42.9%) and male (71,4%) for gender. The average number of NLR was in 7.33 after one-step procedure and 2.77 for multi-step procedure. This number of NLR both not statistically different neither for the post-operative examination nor the comparison between procedure.